Pertumbuhan Ekonomi dan Ketimpangan Pendapatan Antar Kabupaten/ Kota di Aceh, 2005-2014 - Ervina Yunita (Jurnal Transformasi Administrasi, 2016)
Economic growth in Aceh province as an aggregate is continuesly increasing during the period of 2005 to 2014. The differences of interregional economic growth in Aceh province indicate the disparity of income. The income disparities among regions causing problems of development and economic instability. This study aims to analyze the magnitude of disparities between regions and economic growth incounties/cities and to classifiy areas in Aceh province based on their growth rate and per capita income/contribution .The analytical method used is the analysis of economic growth, typology Klassen, Williamson index. These results explain that there are some areas in Aceh that are inrelatively remote areas. Income disparities between regions in the province of Aceh in 2005-2014 is considered low (<0.5) and has a tendency to increase.